2007
DOI: 10.4218/etrij.07.0207.0082
|View full text |Cite
|
Sign up to set email alerts
|

Feed-Forward Control of Transient Gain Dynamics of an EDFA for Optical Burst Networks

Abstract: ⎯In this letter, we demonstrate a technique for suppression of transients in output bursts of an erbium-doped fiber amplifier (EDFA) in an optical burst network. To suppress the transients, the EDFA is forward-fed by non-fluctuating input utilizing a power-modulated burst control packet channel. Using the technique, we obtained a maximum 1.7 dB reduction in gain transient in the EDFA output, and we transmitted 9.953 Gbps data bursts and 2.488 Gbps burst control packets stably. Keywords⎯OBS, EDFA, transient gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Also, transients create problems in optical burst switching networks due to the abrupt power changes in EDFA input power. A feed‐forward method to suppress the EDFA transients is discussed in .…”
Section: Introductionmentioning
confidence: 99%
“…Also, transients create problems in optical burst switching networks due to the abrupt power changes in EDFA input power. A feed‐forward method to suppress the EDFA transients is discussed in .…”
Section: Introductionmentioning
confidence: 99%
“…Such signal power transients (which occur when channels are turned on/off or rerouted) can cause several undesirable phenomena, such as large bit-error-rate and relaxation oscillations. Automatic gain control (AGC) of EDFA can be either electronic [2][3][4][5][6][7][8][9][10][11][12][13][14]o r all optical [15][16][17][18]. In general, electronic AGC is considered a low cost and long-term reliable procedure, but has difficulty following the gain dynamics because of relatively large-time constants of electronic circuits and EDFA amplifier gain dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach utilises the electronic AGC technique that combines both feedback and feedforward control of EDFA. Feedforward control of EDFA was considered in different set-ups in [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fabric noise has been analyzed by cross-sectional shapes of fibers, fiber type, and weaves to calculate objective factors affecting them [6][7][8]. In addition, the subjective sensations and the physiological responses to fabric sounds have been reported [9][10][11][12]. In these researches, they have used a constant frictional speed (0.04 m/s) to generate fabric noises, and reported that LPT (level pressure of total sound) values of fabric sound for various fabrics such as cotton, silk, wool, and nylon ranged from 34 dB to 62 dB.…”
Section: Introductionmentioning
confidence: 99%